Aerosol Concentrations in Relationship to Local Atmospheric Conditions on James Ross Island, Antarctica - Kavan, Jan; Dagsson-Waldhauserova, Pavla; Renard, Jean Baptiste; Láska, Kamil; Ambrožová, Klára (Frontiers in Earth Science, 2018)
Several important ice-free areas (e.g., Seymour Island, Cape Lamb on Vega Island, Terrapin Hill) are located in the Eastern Antarctic Peninsula region. The largest of these ice-free areas can be found on the Ulu Peninsula, James Ross Island, where this study was undertaken. The Ulu Peninsula covers an area of 312 km2, and has been found to be an important active High Latitude Dust source. In this study, aerosol concentrations and local wind properties are described together with their linkages and typical synoptic situations. The highest aerosol concentrations of 57 μg m-3 for PM10 were detected during high wind speed events that exceeded 10 m s-1, which is also a threshold level for activating local mineral material sources. Surface deposition of dust particles can have significant environmental impacts such as changes in properties of atmosphere or enhanced snow melting.